Cytotoxic Potential of Purified Arginine Deiminase from Streptococcus spp - Rusul Madhat Abdullah; Ruqaya Mohammed Al-Ezzy; Asmaa Ali Hussain (Indian Journal of Forensic Medicine & Toxicology, 2021)
The results that presented in the study were based on collecting one hundred and ten clinical samples of oralcavity, burns and wounds. Primary and secondary diagnositic showed that 14 out of these isolates belongedto Streptococcus spp.. The ability of these isolates in arginine deiminase enzyme production was screenedand the results showed that these isolates were arginine deiminase producers with variable degrees. It hasbeen found that one of these isolates which were Streptococcus mitis S5 had the highest specific activity(0.184 U/mg protein), therefore it was chosen for further study. Results of the optimum conditions forarginine deaminase production reveal that the maximum arginine deaminase production was achieved aftersupplementation of the production medium (pH 7.5) with 1% maltose as carbon source, 1.2% tryptone asnitrogen source, 30mM as arginine concentration and incubated at 37ºC for 18h. Under these conditions,ADI purified in three steps including; precipitation with 70% saturated ammonium sulphate, dialysis then ionexchange chromatography using DEAE- cellulose column and the last step was gel filtration chromatographythroughout Sephadex G150 column. Specific activity of the purified enzyme was increased up to 18 U/mgwith 5 folds of purification and 70.8 % enzyme recovery.